Induction of a Rat Enteric Defensin Gene by Hemorrhagic Shock - Condon, Michael R. (American Society for Microbiology, 1999)
Multicellular organisms utilize a battery of extracellular and cellular mechanisms to defend against microbial infiltration. Among the armamentarium used by the small intestine to defend against microbial invasion are antimicrobial peptides called defensins. We previously have shown that gut barrier function is impaired following hemorrhagic shock, resulting in translocation of bacteria or endotoxin. Using a rat model, we examined the effect of hemorrhagic shock on α-defensin expression. We utilized the anchored reverse transcriptase PCR strategy to isolate a rat enteric defensin cDNA. The cDNA is 406 bases in length and encodes a putative prepro-enteric defensin that we have named rat defensin 5 (RD-5). RD-5 expression is restricted to the small intestine and is specifically localized by in situ hybridization to the Paneth cells. A 10-fold increase in its steady state levels was observed in the distal intestine immediately after the termination of shock. This is the first study to show that enteric defensins are inducible following injury. We suggest that enteric defensins may contribute to the complex and integrated barrier function of the intestinal mucosal surface.